Dimethyl Fumarate Triggers the Antioxidant Defense System in Human Retinal Endothelial Cells through Nrf2 Activation - Federico Manai; Marialaura Amadio (MDPI AG, 2022)
Dimethyl fumarate (DMF) is a well-known activator of Nrf2 (NF-E2-related factor 2), used in the treatment of psoriasis and multiple sclerosis. The mechanism of action consists in the modification of the cysteine residues on the Nrf2-inhibitor Keap1, thus leading to the dissociation of these two proteins and the consequent activation of Nrf2. Considering the paucity of evidence of DMF effects in the context of retinal endothelium, this in vitro study investigated the role of DMF in human retinal endothelial cells (HREC). Here, we show for the first time in HREC that DMF activates the Nrf2 pathway, thus leading to an increase in HO-1 protein levels and a decrease in intracellular ROS levels. Furthermore, this molecule also shows beneficial properties in a model of hyperglucose stress, exerting cytoprotective prosurvival effects. The overall collected results suggest that DMF-mediated activation of the Nrf2 pathway may also be a promising strategy in ocular diseases characterized by oxidative stress. This study opens a new perspective on DMF and suggests its potential repositioning in a broader therapeutical context.